ChemInform Abstract: Asymmetric Aldol Reaction of Dichloroacetaldehyde Catalyzed by Diarylprolinol. Issue 49 (17th November 2016) - Hayashi, Yujiro; Nakamura, Daichi; Yasui, Yusuke; Iwasaki, Kotaro; Chiba, Hiroaki
Abstract: γ, γ‐Dichloro‐β‐hydroxy aldehydes are generated in the first step.